2017
DOI: 10.1002/rnj.264
|View full text |Cite
|
Sign up to set email alerts
|

Research in the Rehabilitation Unit Presents Challenges to Nurse Researchers

Abstract: Clinical nursing research is required to develop an evidence base for practice in the rehabilitation unit. An analysis of the challenges and possible methods of overcoming these challenges is useful to both future investigators and nurses in practice to insure that studies can be carried out effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In this study, rehabilitation nurses were asked about their viewpoints on the relevance of published literature, how helpful the research is, and their ability to understand and implement findings from the literature. Consistent with published literature on the use of research information, our study found that, among the nursing population, seldom did nurses read peer-reviewed research, academic journals, or scholarly research articles, nor did they engage in or conduct research (Bench et al, 2019;Berthelsen & Hølge-Hazelton, 2018;Lam & Schubert, 2019;Rose et al, 2017;Saunders & Vehviläinen-Julkunen, 2016). Although 67% of our participants did not engage with or read the research literature, most of the nurses in this study stated their desire to engage in research.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In this study, rehabilitation nurses were asked about their viewpoints on the relevance of published literature, how helpful the research is, and their ability to understand and implement findings from the literature. Consistent with published literature on the use of research information, our study found that, among the nursing population, seldom did nurses read peer-reviewed research, academic journals, or scholarly research articles, nor did they engage in or conduct research (Bench et al, 2019;Berthelsen & Hølge-Hazelton, 2018;Lam & Schubert, 2019;Rose et al, 2017;Saunders & Vehviläinen-Julkunen, 2016). Although 67% of our participants did not engage with or read the research literature, most of the nurses in this study stated their desire to engage in research.…”
Section: Discussionsupporting
confidence: 79%
“…Culturally speaking, the hierarchical nature of medicine may result in nurses feeling subordinate or underpowered in their efforts to incorporate research into practice ( Bench et al, 2019 ; Berthelsen & Hølge-Hazelton, 2015 , 2018 ; Ryan, 2016 ). In addition, research-oriented nurses may feel like “hybrids” in that they must combine the roles and expectations of both nurses and researchers, sometimes leading to peers perceiving them as engaged in frivolous work ( Berthelsen & Hølge-Hazelton, 2018 , p. 1575; Rose et al, 2017 ). A desire to maintain harmony with colleagues could combine with individual and organizational barriers to limit the feasibility of engaging with research for many nurses ( Chen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To minimize this risk and ensure best practices, it is important to understand the ways a recruitment process should uphold ethical standards. 18 , 19 The individual obtaining informed consent is required to outline the risks and benefits of a study in a neutral manner to ensure that consent is given voluntarily. The process should also be attentive to justice-related considerations because this process aims to foster access to research for all who desire to participate (not merely those who have a healthcare provider who is attentive to what is happening on the research front).…”
Section: Introductionmentioning
confidence: 99%